2012
DOI: 10.1073/pnas.1110730109
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipid signals alter mTOR complex 2 (mTORC2) to diminish insulin signaling

Abstract: Increased flux through the glycerolipid synthesis pathway impairs the ability of insulin to inhibit hepatic gluconeogenesis, but the exact mechanism remains unknown. To determine the mechanism by which glycerolipids impair insulin signaling, we overexpressed glycerol-3-phosphate acyltransferase-1 (GPAT1) in primary mouse hepatocytes. GPAT1 overexpression impaired insulin-stimulated phosphorylation of Akt-S473 and -T308, diminished insulin-suppression of glucose production, significantly inhibited mTOR complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
120
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 38 publications
4
120
1
Order By: Relevance
“…Two previous reports have attempted to demonstrate a role of PA in insulin signaling (34,35). Zhang et al (35) observed an increase in total LPA, PA, and DAG levels and also a modest increase in glucose output in primary mouse hepatocytes from WT mice overexpressing GPAT1.…”
Section: Genders Of Agpat2mentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous reports have attempted to demonstrate a role of PA in insulin signaling (34,35). Zhang et al (35) observed an increase in total LPA, PA, and DAG levels and also a modest increase in glucose output in primary mouse hepatocytes from WT mice overexpressing GPAT1.…”
Section: Genders Of Agpat2mentioning
confidence: 99%
“…Zhang et al (35) observed an increase in total LPA, PA, and DAG levels and also a modest increase in glucose output in primary mouse hepatocytes from WT mice overexpressing GPAT1. However, it is unclear if this is specifically due to PA, LPA, or DAG or a combination of these lipids (Fig.…”
Section: Genders Of Agpat2mentioning
confidence: 99%
“…As indicated above, there is an apparent requirement for an unsaturated fatty acid in order to achieve mTOR complex stability (30,54). Thus, it will be of interest to determine whether there are significant differences in the acyl composition of PA obtained from the different sources.…”
Section: Compensatory Production Of Pa In Response To Metabolic Stresmentioning
confidence: 99%
“…Although this study did not connect the need for desaturated lipids and the dependence of mTOR on PA, it did provide further evidence for a lipid dependence of mTOR and potentially a dependence on desaturated lipids. Coleman and colleagues (54) recently reported that the mTORC2 complex falls apart in the presence of dipalmitoyl-PA, which consists of two saturated fatty acids. This is in stark contrast to the effect of PA containing palmitate (saturated) and oleate (mono-unsaturated), which stabilized both mTORC1 and mTORC2 complexes in cells where PA production by PLD was suppressed (30).…”
Section: Compensatory Production Of Pa In Response To Metabolic Stresmentioning
confidence: 99%
“…In contrast, mTORC2 has a positive effect on glucose uptake and glucose tolerance (30) . Lipid synthesis in the liver may also cause insulin resistance via disruption of mTORC2 signalling (31) . These authors showed that overexpression of acyl-CoA:glycerol 3 phosphate acyl transferase that catalyses the formation of LPA and which is the rate limiting step in TAG synthesis (Fig.…”
mentioning
confidence: 99%